Mirror-Image Equivalence and Interhemispheric Mirror-Image Reversal - Corballis, Michael C. (Frontiers in Human Neuroscience, 2018)
Mirror-image confusions are common, especially in children and in some cases of neurological impairment. They can be a special impediment in activities such as reading and writing directional scripts, where mirror-image patterns (such as b and d) must be distinguished. Treating mirror images as equivalent, though, can also be adaptive in the natural world which carries no systematic left-right bias, and where the same object or event can appear in opposite viewpoints. Mirror-image equivalence and confusion are natural consequences of a bilaterally symmetrical brain. In the course of learning, mirror-image equivalence may be maintained through a process of symmetrization, achieved through homotopic interhemispheric exchange in the formation of memory circuits. Such circuits could not distinguish between mirror images. Learning to discriminate mirror-image discriminations may depend either on existing brain asymmetries, or on extensive learning overriding the symmetrization process. The balance between mirror-image equivalence and mirror-image discrimination may nevertheless be precarious, with spontaneous confusions or reversals, such as mirror writing, sometimes appearing naturally or as a manifestation of conditions like dyslexia.